Superconductors for fusion: a roadmap. (13th September 2021) - Mitchell, Neil; Zheng, Jinxing; Vorpahl, Christian; Corato, Valentina; Sanabria, Charlie; Segal, Michael; Sorbom, Brandon; Slade, Robert; Brittles, Greg; Bateman, Rod; Miyoshi, Yasuyuki; Banno, Nobuya; et al.
Abstract: With the first tokamak designed for full nuclear operation now well into final assembly (ITER), and a major new research tokamak starting commissioning (JT60SA), nuclear fusion is becoming a mainstream potential energy source for the future. A critical part of the viability of magnetic confinement for fusion is superconductor technology. The experience gained and lessons learned in the application of this technology to ITER and JT60SA, together with new and improved superconducting materials, is opening multiple routes to commercial fusion reactors. The objective of this roadmap is, through a series of short articles, to outline some of these routes and the materials/technologies that go with them.